The Liability of Land Deed Officials For The Embezzlement Of Duties On The Acquisition Of Rights Over Land - Mohamad Bima Dwika; Anthon F. Susanto; Deden Sumantry (Magister Kenotariatan Universitas Pasundan, 2026)
Land Deed Officials play a pivotal role in land transactions, particularly in the preparation of authentic deeds that serve as the legal basis for the transfer of rights over land. In practice, PPATs frequently receive deposits from taxpayers for the payment of the Duty on the Acquisition of Rights over Land and Building). Cases have nevertheless emerged in which PPATs have abused this authority by embezzling the BPHTB funds entrusted to them. This study aims to analyse the legal liability of the PPAT in cases of BPHTB embezzlement and its juridical implications. A normative juridical method with a descriptive-analytical specification is employed, drawing on the relevant statutory regulations and a case study of the decision of the Semarang District Court No. 738/Pid.B/2018/PN Smg. The findings show that the embezzlement of BPHTB by a PPAT fulfils the elements of the criminal offence of embezzlement under Articles 372 and 374 of the Indonesian Criminal Code. The conduct also constitutes a breach of the professional code of ethics, attracting administrative sanctions up to and including revocation of the PPAT licence. In more complex cases, the PPAT may further be charged under the Anti-Money Laundering Law and the Anti-Corruption Law where state financial losses can be established. The study underlines the need for stricter supervision over the practice of BPHTB deposits with PPATs and improved legal literacy among taxpayers regarding the direct payment of taxes. Regulatory reform is likewise necessary to provide legal certainty as to the boundaries of PPAT authority in the handling of tax funds.